Stratospheric Moistening After 2000. Issue 8 (22nd April 2022) - Konopka, Paul; Tao, Mengchu; Ploeger, Felix; Hurst, Dale F.; Santee, Michelle L.; Wright, Jonathon S.; Riese, Martin
Abstract: The significant climate feedback of stratospheric water vapor (SWV) necessitates quantitative estimates of SWV budget changes. Model simulations driven by the newest European Centre for Medium‐Range Weather Forecast reanalysis ERA5, satellite observations from the Stratospheric Water and OzOne Satellite Homogenized data set, Microwave Limb Sounder, and in situ frost point hygrometer observations from Boulder all show substantial and persistent stratospheric moistening after a sharp drop in water vapor at the turn of the millennium. This moistening occurred mainly during 2000–2006 and SWV abundances then remained high over the last decade. We find strong positive trends in the Northern Hemisphere and weak negative trends over the South Pole, mainly during austral winter. Moistening of the tropical stratosphere after 2000 occurred during late boreal winter/spring, reached values of ∼0.2 ppm/decade, was well correlated with a warming of the cold point tropopause by ∼0.4 K/decade and can only be partially attributed to El Nino‐Southern Oscillation and volcanic eruptions. Plain Language Summary: Water vapor is an effective greenhouse gas. Human‐induced climate change has led to warmer air in the troposphere, which consequently can hold more moisture, thus enhancing the greenhouse effect. The long‐term change in stratospheric water vapor (SWV) is less clear and currently under debate. Using satellite observations, balloon soundings and model simulations, we find an increase of SWV after 2000. This moistening occurred mainly during 2000–2006 and the stratospheric moisture content then remained high over the last decade. The increase of SWV is stronger in the Northern than in the Southern Hemisphere. Over the South Pole, a weak decrease was found. Moistening of the tropical stratosphere occurred mainly during late winter and spring, and was in line with warming of the tropical tropopause, the coldest region that separates the troposphere and stratosphere. Natural causes such as volcanic eruptions cannot completely explain this stratospheric moistening. Key Points: Stratospheric moistening after 2000 is clearly detectable in ERA5‐driven simulations, satellite and in situ observations Hemispheric asymmetry is found with strong positive trends in the Northern Hemisphere and weak negative trends over the South Pole Moistening of the lower tropical stratosphere is only partially caused by El Nino‐Southern Oscillation and volcanic eruptions